Tales from Shakespeare - Lamb, Charles, 1775-1834; Lamb, Mary, 1764-1847 (Salt Lake City, UT : Project Gutenberg, 1996)
"Tales from Shakespeare" by Charles Lamb and Mary Lamb is a collection of adapted stories based on the plays of William Shakespeare, written in the early 19th century. This work aims to introduce younger readers to Shakespearean literature by retaining, as much as possible, the original language of the plays while simplifying the narratives to make them more accessible. The tales cover various plays, including "The Tempest," "Hamlet," "A Midsummer Night's Dream," and "Much Ado About Nothing," weaving in essential themes of love, jealousy, and reconciliation through characters such as Prospero, Miranda, and Beatrice. The opening portion of the text provides a preface in which the authors explain their goal of making Shakespeare's works relatable to children, indicating that they have taken great care to maintain the integrity of Shakespeare's language while tailoring the narratives. The collection begins with "The Tempest," describing the isolated lives of Prospero and his daughter Miranda on an enchanted island, unfolding their deep connection and the magical events surrounding them. Prospero, a duke wronged by his brother, uses his magical abilities to orchestrate a storm that brings his enemies to the island, while showcasing his complex relationship with magical spirits like Ariel and the grotesque creature Caliban. Here's an introduction to a world of intrigue and exploration of human emotions, serving as a charming doorway into the larger body of Shakespeare's work. (This is an automatically generated summary.)
The tempest -- A midsummer night's dream -- The winter's tale -- Much ado about nothing -- As you like it -- The two gentlemen of Verona -- The merchant of Venice -- Cymbeline -- King Lear -- Macbeth -- All's well that ends well -- The taming of the shrew -- The comedy of errors -- Measure for measure -- Twelfth night; or, what you will -- Timon of Athens -- Romeo and Juliet -- Hamlet, Prince of Denmark -- Othello -- Pericles, Prince of Tyre.
Release date is 1996-06-01
Tokuya Matsumoto
Keywords: Shakespeare, William, 1564-1616 -- Adaptations; Shakespeare, William, 1564-1616 -- Stories, plots, etc. -- Juvenile literature